Metode Show and Tell dalam Membangun Kepercayaan Diri Siswa Sekolah Dasar pada Pembelajaran Seni Budaya - Wibowo, Yusuf Rendi; Salfadilah, Fatonah (TADRUSUUN: JURNAL PENDIDIKAN DASAR, 2026)
Developing self-confidence is a crucial aspect of affective growth for elementary school students, particularly in the context of arts education. Many students possess artistic talent but experience hesitation or anxiety when presenting their work publicly, limiting the full expression of their creativity. This study aims to describe the implementation of the Show and Tell method in fostering self-confidence among fourth-grade students during cultural arts lessons. A qualitative descriptive approach was employed, involving one teacher and students at SDN 1 Way Mili during the first semester of the 2024/2025 academic year. Data were collected through observation of students’ gestures and expressions during presentations, documentation of artworks and classroom activities, and interviews with both the teacher and students. The findings indicate that the Show and Tell method effectively enhances students’ courage to present, their pride in their own creations, and their ability to articulate the meaning behind their works. Teacher support, including verbal encouragement, emotional guidance, and structured practice, played a significant role in reducing anxiety and promoting active participation. The study concludes that integrating Show and Tell into cultural arts lessons provides students with opportunities to express themselves creatively and verbally, thereby strengthening self-confidence, emotional expression, and social interaction. These results suggest that experiential and supportive approaches in arts education can contribute to the holistic development of students’ affective and interpersonal skills.